Responsibility of Perpetrators of Murder with Same-Sex Romance Motive (Study of Decision Number: 64/Pid.B/2022/PN. Kot) - Recca Ayu Hapsari; Zikri Aldino Z. P (Yayasan Adra Karima Hubbi, 2024)
Background. It is hoped that the judge will give a severe criminal verdict against the perpetrators of the crime of murder in order to have a deterrent effect on the perpetrators of the crime. Purpose. Gambling is a prohibited act as stipulated in Article 303 of the Criminal Code, 303 bis of the Criminal Code, and Article 27 paragraph (2) of the Law on information and electronic transactions. In verdict number 233/Pid.B/2022/Pn.Cbd the author found a discrepancy in the application of the article, so the problem in this study is